1992
DOI: 10.1016/0018-506x(92)90040-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, endocrine, and immunological correlates of immigration by an aggressive male into a natural primate group

Abstract: A very aggressive young adult male entered one of three long-term study groups of yellow baboons, Papio cynocephalus, approximately 3 weeks after an immobilization project began. The immigrant male's rate of agonistic encounters was appreciably higher than average, and these interactions disproportionately involved adult females as targets. Basal cortisol concentrations were higher and total lymphocyte counts lower for individuals immobilized during the immigration situation than for other individuals; these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
4

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(97 citation statements)
references
References 31 publications
6
87
4
Order By: Relevance
“…Second, although two studies of East African baboons have reported an increase in abortion rates in some early pregnant females following male immigration (Pereira 1983, Alberts et al 1992, no cases of abortion following male immigration have been observed in our study group. Instead, infant mortality is due to infanticide that occurs largely during the first few months after the immigrant male starts to challenge the alpha position.…”
Section: Events During the Time Of Male Rank Instabilitycontrasting
confidence: 82%
“…Second, although two studies of East African baboons have reported an increase in abortion rates in some early pregnant females following male immigration (Pereira 1983, Alberts et al 1992, no cases of abortion following male immigration have been observed in our study group. Instead, infant mortality is due to infanticide that occurs largely during the first few months after the immigrant male starts to challenge the alpha position.…”
Section: Events During the Time Of Male Rank Instabilitycontrasting
confidence: 82%
“…Together, these correlates of high rank, especially alpha status, may suppress immune function. In support, previous research has found that high-ranking male baboons have higher parasite loads, and one highly aggressive alpha male had a low white blood cell count (48,49).…”
supporting
confidence: 68%
“…These results are somewhat surprising in the context of other studies on status-related differences in health in male vertebrates, including research on baboons in Amboseli (48,49). In several species, testosterone has been proposed to mediate the tradeoff between reproductive effort, survival, and immune function (17,61).…”
Section: Discussioncontrasting
confidence: 43%
“…For instance, in water striders hyper-aggressive males cause a breakdown of mating activity in the whole population compared with populations without extreme individuals under laboratory conditions (Sih & Watters 2005). In yellow baboons, one hyperaggressive male immigrant caused various deleterious effects on other group members, such as abortions by three pregnant females following constant harassment and a considerable increase in stress hormone levels in all group members (Alberts et al 1992). In humans, extremely non-cooperative individuals that relentlessly exploit others often fall into the category of 'sociopaths' or 'psychopaths' (Blair 2006;Blair et al 2006;Hare & Neumann 2008).…”
Section: How Does Personality Affect the Evolution And Maintenance Ofmentioning
confidence: 99%